Knowledge Levels, Cutlery Management and Number of Germs on Toddler Cutleries - Dyah Suryani; Wibowo Wibowo (Alliance oh Health Activists (AloHA), 2019)
Background: Cleanliness of toddler feeding utensils that have low immune system / susceptibility to the exposure of disease is a very important part and influences the quality of food and drinks. Cutlery sanitation aims to kill vegetative microbial cells left on the surface of the appliance. Washing and cleaning utensils are very important in food processing and inseparable part of the principles of food preservation. The use of cutlery that is determined or determined by the Ministry of Health in 2004 is the total number of tableware germ that is ≤ 100 colonies / cm2 from the surface of the equipment being examined. The purpose of this study was to determine the relationship between the level of knowledge and management of eating utensils with the number of germs counts in toddler cutlery in Blawong I Sub-village, Bantul. Methods: The type of this research is analytic observational research with laboratory tests and cross-sectional research designs. The sampling technique used in the study is probability samples or random samples. The sample in this study were mothers who have children under five in Blawong I Sub-village, Bantul. The research instrument used was a laboratory test and a research questionnaire. Data analysis used univariate and bivariate analysis and the Fisher's Exact Test as an alternative test. Results: There was found the relationship between the level of knowledge with the number of germs in the tableware of Blawong I Bantul sub-village with a value of p = 0.011 (